(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
Internationalization is seen as a crucial tactic for countries transitioning from central planning to market-driven economies. Both national and institutional efforts are underway to internationalize universities. However, there’s a lack of research on how individual institutions undertake internationalization and the benefits they derive. This study explores how Uzbek universities utilize internationalization to improve the knowledge and skills of their teachers and students. The findings indicate that the current methods of internationalization in Uzbek universities are characterized by an ad hoc approach, with constraints such as limited resources and language proficiency among staff and students. Consistent with prior research, inadequate resources and insufficient English proficiency among educators and learners are identified as significant barriers to internationalization efforts. Additionally, a novel concern highlighted in this study, not previously addressed in relevant literature, pertains to the sustainability of knowledge generation through research and publications.